Borderline personality disorder and psychosis: a review - Barnow, Sven; Arens, Elisabeth A.; Sieswerda, Simkje; Dinu-Biringer, Ramona; Spitzer, Carsten; Lang, Simone (Current psychiatry reports, 2010)
Early views of borderline personality disorder (BPD) were based on the idea that patients with this pathology were “on the border” of psychosis. However, more recent studies have not supported this view, although they have found evidence of a malevolent interpersonal evaluation and a significant proportion of BPD patients showing psychotic symptoms. For example, in one study, 24% of BPD patients reported severe psychotic symptoms and about 75% had dissociative experiences and paranoid ideation. Thus, we start with an overview regarding the prevalence of psychotic symptoms in BPD patients. Furthermore, we report findings of studies investigating the role of comorbidity (eg, post-traumatic stress disorder) in the severity and frequency of psychotic symptoms in BPD patients. We then present results of genetic and neurobiological studies comparing BPD patients with patients with schizophrenia or nonschizophrenic psychotic disorders. In conclusion, this review reveals that psychotic symptoms in BPD patients may not predict the development of a psychotic disorder but are often permanent and severe and need careful consideration by clinicians. Therefore, adequate diagnosis and treatment of psychotic symptoms in BPD patients is emphasized.
Gesehen am 02.12.2022